Correlation between EFL Students’ Speaking Anxiety and Self-Efficacy in Public Speaking Class at English Department of Universitas Negeri Padang - Annisa Qurnia; Leni Marlina (Journal of English Language Teaching, 2020)
This study investigated the correlation between EFL students speaking anxiety and self-efficacy. The participants of this study were 63 students of Public Speaking class at English Department of UNP in academic year 2018. Two questionnaires were administered to the students to measure the correlation between the two aspects. The questionnaires were Foreign Language Speaking Anxiety Scale and General and Academic Self-Efficacy Scale. The results show that there is positive correlation between EFL students’ speaking anxiety and self-efficacy. The correlation between the two aspects are low, significant, and in the same direction. Students’ speaking anxiety and self-efficacy stand in the medium level. They are not high and also not low. Based on gender, there is no significant differences between female and male speaking anxiety. And, the female and male’s speaking self-efficacy also do not have significant differences. Key words: Speaking, Speaking Anxiety, Speaking Self-Efficacy